Impaired SMAD1/5 Mechanotransduction and Cx37 (Connexin37) Expression Enable Pathological Vessel Enlargement and Shunting. Issue 4 (April 2020) - Peacock, Hanna M.; Tabibian, Ashkan; Criem, Nathan; Caolo, Vincenza; Hamard, Lauriane; Deryckere, Astrid; Haefliger, Jacques-Antoine; Kwak, Brenda R.; Zwijsen, An; Jones, Elizabeth A.V.
Abstract : Objective: Impaired ALK1 (activin receptor–like kinase-1)/Endoglin/BMP9 (bone morphogenetic protein 9) signaling predisposes to arteriovenous malformations (AVMs). Activation of SMAD1/5 signaling can be enhanced by shear stress. In the genetic disease hereditary hemorrhagic telangiectasia, which is characterized by arteriovenous malformations, the affected receptors are those involved in the activation of mechanosensitive SMAD1/5 signaling. To elucidate how genetic and mechanical signals interact in AVM development, we sought to identify targets differentially regulated by BMP9 and shear stress. Approach and Results: We identify Cx37 (Connexin37) as a differentially regulated target of ligand-induced and mechanotransduced SMAD1/5 signaling. We show that stimulation of endothelial cells with BMP9 upregulated Cx37, whereas shear stress inhibited this expression. This signaling was SMAD1/5-dependent, and in the absence of SMAD1/5, there was an inversion of the expression pattern. Ablated SMAD1/5 signaling alone caused AVM-like vascular malformations directly connecting the dorsal aorta to the inlet of the heart. In yolk sacs of mouse embryos with an endothelial-specific compound heterozygosity for SMAD1/5, addition of TNFα (tumor necrosis factor-α), which downregulates Cx37, induced development of these direct connections bypassing the yolk sac capillary bed. In wild-type embryos undergoing vascular remodeling, Cx37 was globally expressed by endothelial cells but was absent in regions of enlarging vessels. TNFα and endothelial-specific compound heterozygosity for SMAD1/5 caused ectopic regions lacking Cx37 expression, which correlated to areas of vascular malformations. Mechanistically, loss of Cx37 impairs correct directional migration under flow conditions. Conclusions: Our data demonstrate that Cx37 expression is differentially regulated by shear stress and SMAD1/5 signaling, and that reduced Cx37 expression is permissive for capillary enlargement into shunts. Abstract : Supplemental Digital Content is available in the text.